Bimbingan dan Konseling Belajar (Akademik) dalam Perspektif Islam - Yuni Novitasari; Muhammad Nur (Universitas Mathla'ul Anwar Banten, 2017)
The goal of national education as set forth in the Law of the Republic of Indonesia looks not only focused on the development of cognitive but also affective, and psychomotor. To realize the quality of the knowledge of the learner, the learning experience (academic) becomes so important. Learning gains are not limited to the cognitive but also the character of the students. Learning is a way to acquire knowledge is a precious suggestion in Islam. The subject teachers as facilitators in helping students learn. Similarly, guidance and counseling teachers, in the field of academic, guidance and counseling teacher seeks to help learners to understand themselves and their environment so that learners are able to adapt and fulfill the task of learning (academic) it well. This study aims to produce a study on the Islamic perspective regarding guidance and counseling learning (academic). The method used is the study of literacy. With reviewing or studying libraries or literacy, both print and electronic that have a study on the topic. Based on the results of the study, it can be concluded that the counseling and guidance of learning (academic) aims to help facilitate the individual in the learning process. So in the view of Islam, teacher guidance and counseling have a glorious opportunity to teach goodness and benefits for other people especially in the study.